Skin Failure Among Critically Ill Patients Afflicted with Coronavirus Disease 2019 (COVID-19). (October 2021) - Greenway, Andrew; Leahy, Nicole; Torrieri, Lisa; An, Anjile; Fink, Sarah A.; Witenko, Corey; Shikar, Morgan; Winchell, Robert J.; Barie, Philip S.; Liu, Susan I.
Objective: To characterize skin integrity among coronavirus disease 2019 (COVID-19) patients treated in the intensive care unit (ICU), and identify risk factors for skin failure (SF) in these patients.Design: The characteristic, profound pro-inflammatory, hypercoagulable state of COVID-19 is manifested by the high severity of illness and extensive organ dysfunction observed in these patients. SF in critically ill patients, although described previously, exhibits a uniquely complex pathogenesis in this population.Patients: Retrospective review of all COVID-19 patients (confirmed positive for severe acute respiratory syndrome coronavirus-2 [SARS-CoV-2]) admitted to a single surgical ICU for at least 48 hours between March-June 2020.Interventions: Data were extracted from a COVID-19 institutional data repository that harvested data from electronic health records and other clinical data sources. Demographics; coagulation/inflammation biomarkers; number, location, and stage of SF lesions; resource utilization; and outcomes were captured.Measurements and Main Results: 64 patients met inclusion criteria; 51 (80%) developed SF (SF+ ). Forty-three (85%) developed stage 3 or higher SF (χ 2   =  22.66, P  < .0001). Thirty-nine of 51 (76%) SF+ patients developed more than one SF lesion (χ 2   =  13.26, P   =  .0003). SF+ patients manifested a profound pro-inflammatory, hypercoagulable phenotype (lower serum albumin and higher ferritin, interleukin [IL]-6 and D-dimer concentrations [all, P  < .001]). Durations of mechanical ventilation, vasopressor therapy, and ICU length of stay were significantly longer (all, P  < .05) in the SF + patients.Conclusions: The unique characteristics of COVID-19 dermatopathology and the strong correlation between markers of inflammation and development of SF reflect COVID-19-related organ dysfunction and its deleterious effects on the microcirculation. Considering that skin is invaded directly by SARS-CoV-2 and affected by COVID-19-related immune complex deposition and microthrombosis, SF may reflect disease as opposed to pressure injuries related to processes of care. In the context of COVID-19 critical illness, SF should not be considered a "never event."